Identifying Cultural Diplomacy and Sustainable Development in Sister Province Cooperation of Bali, Indonesia - Anak Agung Mia Intentilia (Pusat Kajian Bali Universitas Udayana, 2024)
While States have traditionally formed the focus of International Relations studies, the contributions of local government actors have become increasingly important in both influencing and responding to the forces of global politics, including in the Global South. In this vein, this preliminary study explores the practice of the local government in initiating sister province cooperation in Bali, Indonesia. This study uses three conceptual frameworks: paradiplomacy, sustainable development, and critical discourse analysis. Primary data were collected through interviews with relevant local government officials in Bali and secondary data were gathered from academic articles, official websites, and online news items. This paper identified two most prominent sectors of this cooperation, namely: tourism and culture. These two areas align with the United Nations Sustainable Development Goals (SDGs). While clearly connected with governmental and international goals, challenges remain in implementing sister province cooperation, achieving continuity among the parties involved, and dealing with funding limitations.